2015
DOI: 10.1007/s00403-015-1558-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical glucocorticoid or pimecrolimus treatment suppresses thymic stromal lymphopoietin-related allergic inflammatory mechanism in an oxazolone-induced atopic dermatitis murine model

Abstract: Congenitally or early impaired skin barrier as the first event starting the 'atopic march' in atopic dermatitis (AD) patients can increase allergen penetration that results in sensitization, even in the airways, followed by asthma and allergic rhinitis. Thymic stromal lymphopoietin (TSLP) is a cytokine existing in high levels in AD skin and is considered as a novel therapeutic target for atopic disease. We generated oxazolone (Ox)-induced AD-like (Ox-AD) hairless mice and divided them into four groups accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We have already done an experiment using topical corticosteroid in other study2230. Through the results of these both experiments, we have confirmed that acidification of skin had comparable effect for skin permeability barrier as topical corticosteroid, so we did not use positive control in this study.…”
Section: Discussionmentioning
confidence: 75%
“…We have already done an experiment using topical corticosteroid in other study2230. Through the results of these both experiments, we have confirmed that acidification of skin had comparable effect for skin permeability barrier as topical corticosteroid, so we did not use positive control in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Tacrolimus is a calcineurin antagonist that inhibits the transcription of inflammatory cytokines released from T‐cells and mast cells via binding to FK‐binding protein and blocking calcineurin phosphatase activity. Tacrolimus also suppresses the expression of cytokines such as proteinase‐activated receptor‐2 and thymic stromal lymphopoietin, both of which are involved in allergic Th2 responses and itch sensation (Grassberger et al, ; Hanifin & Chan, ; Reynolds & Al‐Daraji, ; Yoon, Jung, Kim, Lee, & Choi, ). In a prospective, open, multicenter, investigator‐driven trial of 29 adult patients with occupationally induced hand dermatitis (OHD) due to irritant exposure, application of tacrolimus 0.1% ointment twice daily for 4 weeks resulted in 44% of patients with complete clearance, and additional 67% of the patients attaining at least 50% improvement, based on the Jena HE Score, which calculates severity based on area affected by vesicles, erythema, scaling, infiltration, lichenification, and fissuring (Schliemann et al, ).…”
Section: Topical Agentsmentioning
confidence: 99%
“…Topical treatment with mid-potent GC has been shown to improve the AD-like skin lesion and barrier impairment by suppressing inflammation [33]. In line with this, Chiba et al [4] demonstrated that topical GC could reverse PPARa expression in NC/Nga AD-like mice skin, accompanied with amelioration of inflammation.…”
Section: Discussionmentioning
confidence: 92%